Multicenter 3-arm randomized controlled trial comparing efficacy of topical honey alginate versus topical pure natural honey, versus best supportive oral care in the management of radiation mucositis among patients under oin radical radiotherapy for nasopharyngeal cancer - Biswal, Biswa Mohan (Pusat Pengajian Sains Perubatan, Universiti Sains Malaysia, 2011)
Introduction: Radiation mucositis is an acute toxicity of ionizing radiation to the oropharyngeal mucosa, for which no specific treatment seems appropriate.The pathology involves a cascade of biological events with molecular and inflammatory intermediates complicated by infection. The ultimate end result being ulceration, pain and dysphagia. The above universal symptom results in enormous hospital cost and poor compliance to radiotherapy. Amongst the agents studied, pure natural honey is one of the evidence based agent found to reduce extent of mucositis. Materials and Method: This is a prospective randomized study comparing the effects of pure natural Manuka honey, honey-alginate and best supportive oral care in radiation mucositis induced by concurrent chemo-radiotherapy for the treatment of nasopharyngeal carcinoma. 90 patients with nasopharyngeal cancers were treated with concurrent chemoradiotherapy. The patients were assigned to topical pure natural Manuka honey (n=30), honey-alginate pastille (30), and best supportive oral care. The EORTC QLQ C30, EORTC H&N QLC C35, RTOG acute toxicity scale, and Oral Mucositis Assessment Scale (OMAS) were evaluated along with lean body weight. Results: In this analysis 72 patients were evaluable; i.e. 23 patients were treated with best supportive care, 23 with honey-alginate pastille and 26 with topical pure Manuka honey. The median age was 47 years (range 18-73), and there were 56 males and 16 females distributed amongst Malay ( 48%), Chinese (30%), and other races (22%). Stage III patients were majority (63%). Total 7-cycles of chemotherapy could be delivered to 39%, 82% and 65% of patients in BSC, honey-alginate and pure honey group of patients. Full course of study agent was completed in 87% of honey-alginate group and 76% ofManuka honey group. The main side-effects of study agent were nausea, vomiting and burning sensation the mucosa leading to discontinuation of study agents in some participants. The grade-II RTOG mucositis was higher amongst best supportive care group compared to patients on honey algiruite. All groups of patients showed loss of body weight but none showed statistically significant superiority over others. Conclusions: There was marginal benefit of honey-alginate over Manuka honey and best supportive oral care in the prevention of radiation mucositis. Weight loss was a significant problem equally observed in three groups. Further studies are necessary to improve flavor of honey, adding Royal jelly and to use of anesthetics plus anti-emetic for acceptance of honey application during mucositis phase of radiotherapy